Gluten-free bakery products of high nutritional value - Drobot, Vira; Shevchenko, Anastasiia; Sorochynska, Yuliia (My University, 2021)
In the paper attention was paid to the chemical composition of sorghum flour, meal of pumpkin seed kernels, micellar casein and whey, as raw materials that can increase the nutritional value of gluten-free bread. It was established that the use of these raw materials as sources of physiologically functional substances improved the organoleptic properties of products, their aroma, preservation of freshness. The nutritional value of protein, dietary fiber, minerals and vitamins increased. The digestibility of these products improved.
Keywords: gluten-free; bread; consumer properties; nutritional value; кафедра технології хлібопекарських і кондитерських виробів